Interferência do hipoclorito de sódio na absorção de macro e micronutrientes nas culturas da soja e do feijão - Cardoso da Silva, Jose Iran [UNESP]; Fernandes, Dirceu Maximino [UNESP]; Rocha Pereira, Maria Renata [UNESP]; Leles, Erica Pontes [UNESP]; da Silva Pereira, Francisco Rafael [UNESP]; Silva Cruz, Simerio Carlos [UNESP] (Universidade Federal de Uberlândia (UFU), 2010)
The objective of this work was to evaluate the effect of the sodium hypochlorite application in different levels in the fresh and dry biomass and in the uptake of macronutrients and micronutrients in plants of soybean and bean. The experiments were carried at the greenhouse of the "Departamento de Recursos Naturais/Ciência do Solo, FCA/UNESP, Botucatu/SP", in columns of rigid PVC with capacity to 1.0 liter of soil. The experimental design used in each experiment was entirely randomized, with 4 replications. The treatments in each experiment were constituted of 5 doses of sodium hypochlorite (0.0, 0.5, 1.0, 2.0 and 4.0 L ha(-1)). The following parameters were evaluated: fresh and dry biomass, macro and micronutrients contents in the plants leaves. The levels of sodium hypochlorite did not reflect significantly on the fresh and dry biomass of soybean and bean. The soybean dry biomass presented significant difference among the level of sodium hypochlorite. Average contents of macro and micronutrients obtained in bean leaves were not affected by the levels of sodium hypochlorite. The sulphur contents in soybean leaves presented significant difference. The sodium hypochlorite did not affect negatively the macro and micronutrients contents in leaves of soybean and bean.

O presente trabalho objetivou avaliar o efeito da aplicação do hipoclorito de sódio em diferentes doses na biomassa fresca e seca e nos teores macro e micronutrientes nas folhas das culturas da soja e do feijão. Os experimentos foram conduzidos em casa de vegetação do Departamento de Recursos Naturais/Ciência do Solo, FCA/UNESP, Botucatu/SP. O delineamento experimental utilizado em cada experimento foi o inteiramente casualizado, com 4 repetições. Os tratamentos foram constituídos de 5 doses de hipoclorito (0,0; 0,5 L ha-1; 1,0 L ha-1; 2,0 L ha-1 e 4,0 L ha-1). Avaliou-se: biomassa fresca e seca, teores de macro e micronutrientes nas folhas das plantas. Não se observou sintoma de toxidez e as doses de hipoclorito não refletiram significativamente nas biomassas frescas e secas das plantas de feijão. A biomassa seca da cultura da soja apresentou diferença significativa entre as doses de hipoclorito. Os teores médios de macro e micronutrientes obtidos nas folhas do feijoeiro, não foram afetados pelas doses de hipoclorito. Os teores de enxofre e de magnésio nas folhas das plantas de soja apresentaram diferença significativa. O hipoclorito não afetou negativamente os teores de macro e micronutrientes nas folhas das culturas da soja e do feijão.
Sodium hypochlorite interference in the uptake of macronutrients and micronutrients in the soybean and bean crops
Keywords: Glycine max (L.); Phaseolus vulgaris L; NaClO; Nutrients text